Persepsi Pengunjung Tentang Komponen Daya Tarik Wisata Pulau Pigago Pasaman Barat - Alghifari, Wildan; Wulandari, Dwi Pratiwi (Departemen Pariwisata Universitas Negeri Padang, 2024)
This research was motivated by the problem of visitors' perceptions regarding the tourist attraction of Pigago Island, West Pasaman. This research uses a descriptive quantitative survey method. The research was conducted on Pigago Island, West Pasaman. The total population in the study was 12,941 people with a sample of 100 respondents. Data collection used a questionnaire with a Likert scale. Using descriptive analysis and clarification of interval class scores using the SPSS version 25.00 program. Based on the research results, it is known that the overall indicator data with a result of 157.16 is categorized as quite good. The attraction indicator with a result of 54.58 is categorized as quite good, the facilities indicator with a result of 47.32 is categorized as bad, the accessibility indicator with a result of 52.78 is categorized as quite good, the supporting services indicator with a result of 46.91 is categorized as bad. So it can be concluded that visitors' perceptions of the tourist attraction components of West Pasaman Pigago Island are quite good